Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1038/415192a
|View full text |Cite
|
Sign up to set email alerts
|

The motor domain determines the large step of myosin-V

Abstract: Class-V myosin proceeds along actin filaments with large ( approximately 36 nm) steps. Myosin-V has two heads, each of which consists of a motor domain and a long (23 nm) neck domain. In accordance with the widely accepted lever-arm model, it was suggested that myosin-V steps to successive (36 nm) target zones along the actin helical repeat by tilting its long neck (lever-arm). To test this hypothesis, we measured the mechanical properties of single molecules of myosin-V truncation mutants with neck domains on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
77
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(86 citation statements)
references
References 27 publications
6
77
3
Order By: Relevance
“…The attachment lifetime at 2 mM ATP (0.12 s) is shorter than that at 1 M ATP concentration (0.52 s). The value at 2 mM ATP is consistent with the V max of the actin-activated Mg-ATPase and the expected dwell time (0.11 s) from Tanaka et al (20) if S1 is not a processive molecule. At 1 M ATP the lifetime is longer as expected for a second order reaction at low substrate concentration.…”
Section: Characterization Of Expressed Myosin Iq Mutant-to Exam-supporting
confidence: 69%
“…The attachment lifetime at 2 mM ATP (0.12 s) is shorter than that at 1 M ATP concentration (0.52 s). The value at 2 mM ATP is consistent with the V max of the actin-activated Mg-ATPase and the expected dwell time (0.11 s) from Tanaka et al (20) if S1 is not a processive molecule. At 1 M ATP the lifetime is longer as expected for a second order reaction at low substrate concentration.…”
Section: Characterization Of Expressed Myosin Iq Mutant-to Exam-supporting
confidence: 69%
“…This value is similar to the step size (36 nm) of myosin Va (13,15). Therefore, it is reasonable to assume that myosin Vb moves on actin filaments with large steps in a manner similar to that of myosin Va.…”
Section: Discussionsupporting
confidence: 56%
“…This processive behavior is consistent with the function of myosin Va in the cell as a cargo transporter (9). A finding critical to understand the mechanism of processive movement of myosin Va is the extremely large step size of myosin Va (13,15,16). Because myosin Va has an extremely long neck domain, it was proposed that myosin Va moves with a handover-hand mechanism in which myosin heads span a helical repeat of the actin filament with its long neck and walk straight along it with one head attached and the other head dissociated (17)(18)(19).…”
mentioning
confidence: 99%
“…Yanagida and co-workers created a myosin V construct with a shorter lever arm and they observed that the step size does not change with a decreasing length of the lever arm. 47 (The same experiment was then repeated by using similar constructs and it was shown that the step size depends on the length of the lever arm 19 ). 4.…”
Section: The Challengementioning
confidence: 99%